Implementation Strategy and Financing Scheme for Scheduled Feed Sludge Services (LLTT) to Support Regional Development in Deli Serdang Regency, Deli Serdang Province North Sumatra - Sahri Muda; Cut Nuraini; Ruth Riah Ate Tarigan (PT. Publikasiku Academic Solution, 2026)
This study examines the implementation strategy and financing scheme of Scheduled Fecal Sludge Services (LLTT) in supporting regional development in Deli Serdang Regency, Indonesia. The background of this research is the persistent sanitation problem in rapidly growing urban and peri-urban areas, where inadequate fecal sludge management still poses environmental and public health risks. The objective of this study is to analyze the implementation process of LLTT and to formulate an effective and sustainable financing model to support sanitation service delivery. The research employs a qualitative descriptive method with data collected through observation, in-depth interviews, and documentation involving government officials, service operators, community users, and related stakeholders. Data were analyzed using policy implementation theory (Edwards III model) and financing scheme analysis, including full cost recovery, partial subsidy, cross-subsidy, and public–private partnership (PPP) approaches. The results show that LLTT implementation is influenced by communication, resources, disposition, and bureaucratic structure, while financing remains the most critical factor for sustainability. The partial subsidy model is identified as the most feasible approach, supported by cross-subsidy and potential PPP collaboration. In conclusion, LLTT implementation in Deli Serdang is strategically positioned for growth but requires stronger institutional coordination, improved infrastructure, and innovative financing mechanisms to ensure long-term sustainability and regional development impact.